2006
DOI: 10.3928/1081-597x-20060401-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pupil Dynamics After Implantation of Artisan Phakic Intraocular Lenses

Abstract: PURPOSE:To compare pre-and postoperative horizontal and vertical pupil diameters after horizontal Artisan phakic intraocular lens (PIOL) (Ophtec BV, Groningen, The Netherlands) implantation for correction of myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…8,11,21 The pupil ovalization might be explained mechanically by asymmetric enclavation or by enclavation of the haptics in the more central iris. Bootsma et al 22 found a restriction in pupil dilation in the horizontal axis after horizontal Artisan/Verisyse pIOL implantation that was attributed to mechanically induced prevention of pupil dilation by the iris claw.…”
Section: Discussionmentioning
confidence: 98%
“…8,11,21 The pupil ovalization might be explained mechanically by asymmetric enclavation or by enclavation of the haptics in the more central iris. Bootsma et al 22 found a restriction in pupil dilation in the horizontal axis after horizontal Artisan/Verisyse pIOL implantation that was attributed to mechanically induced prevention of pupil dilation by the iris claw.…”
Section: Discussionmentioning
confidence: 98%
“…These include retinal detachment, 9,10 traumatic aniridia, 11 IOL dislocation, 12,13 pigment dispersion syndrome, 14 endothelial cell loss, 15 and glaucoma. 16 One concern is that pIOLs that are fixated to the iris inevitably cause postoperative intraocular structure alterations such as pupil ovalization, 17 pupil size change, 18 anterior chamber depth (ACD) change, 19,20 and crystalline lens rise. 14 Although anterior segment analyses after pIOL implantation have been performed, 14,17,19,20 to our knowledge, the change in the anterior chamber angle has not been reported.…”
mentioning
confidence: 99%
“…16 One concern is that pIOLs that are fixated to the iris inevitably cause postoperative intraocular structure alterations such as pupil ovalization, 17 pupil size change, 18 anterior chamber depth (ACD) change, 19,20 and crystalline lens rise. 14 Although anterior segment analyses after pIOL implantation have been performed, 14,17,19,20 to our knowledge, the change in the anterior chamber angle has not been reported. In this study, we evaluated anterior chamber angle alterations after pIOL implantation and their effect on intraocular pressure (IOP) and anterior chamber inflammation.…”
mentioning
confidence: 99%